Copper-Catalyzed C–N Bond Formation with N-Heterocycles and Aryl Halides - Boswell, Mikki G.; Yeung, Fanny G.; Wolf, Christian (Synlett, 2012)
The microwave-assisted, cuprous oxide catalyzed coupling of aryl bromides and iodides with imidazole, benzimidazole, pyrazole, or triazole was found to give a wide range of N-aryl heteroaromatic products in good to high yields. Aryl dibromides undergo selective monosubstitution even in the presence of large excess of N-heterocyclic nucleophiles which leaves the second aryl bromide functionality intact for further derivatization.
Keywords: copper; cross-coupling; N-heterocycles; aryl halides; microwave